Conducting a national research on health: best methodology and the challenges - Ab Rahman, Jamalludin (2019)
National research simply means a big research which are able to represent a huge population. Research on such scale is always labour intensive and expensive. Survey is the most popular research design adopted for the purpose. However, for any method, serious and meticulous attention must be put during the planning stage. Population must be thoroughly identified and every level of stratification or the varieties of clusters have to be identified. Complex survey sampling method is often used as it will adjust for the design effect. Statistical analysis should be tailored for this weighted population. Challenges start from the planning stage, data collection, analysis, up to the reporting stage. Collaboration from multiple agencies is inevitable. If properly done, information from such study will assist the country to have a good estimate of the burden of disease and will certainly make the policy planning more relevant.